The Effect of Construction Workers’ Work Resilience on Their Leisure Sports Participation: The Mediating Role of Safety and Health Awareness - Yujie Zhang; Shushan Deng; Sen Chen; Zhenning Yao; Yuyang Hou; Qian Huang; Zijian Liu (Buildings)
This study, grounded in psychological capital theory and the work resource model, investigates the impact of construction workers’ work resilience on their leisure sports participation. An interdisciplinary integration model was developed, incorporating work resilience, safety and health awareness, and leisure sports participation, providing empirical evidence for enhancing the well-being of the construction workforce. The study specifically examines the roles of physiological resilience, psychological resilience, social support, and occupational engagement in this context. A survey conducted with 663 construction workers in China and Korea revealed the following: (1) physiological resilience, psychological resilience, social support, and occupational engagement significantly and positively influence workers’ leisure sports participation; (2) safety and health awareness serves as a significant mediator between work resilience and leisure sports participation among construction workers. These findings underscore the importance of improving the work environment and creating semi-natural restorative landscapes to promote the physical and mental health of construction workers, as well as their engagement in leisure sports. The study calls for governmental and community initiatives, including policy support and resource allocation, to comprehensively enhance the overall well-being of construction workers.